Diagnosis of sporadic neurofibromatosis type 2 in the paediatric population. Issue 5 (13th March 2018) - Anand, Geetha; Vasallo, Grace; Spanou, Maria; Thomas, Saumya; Pike, Michael; Kariyawasam, Didu Sanduni; Mehta, Sanjay; Parry, Allyson; Durie-Gair, Juliette; Nicholson, James; Lascelles, Karine; Everett, Vanessa; et al.
Abstract : Objective: Onset of symptoms in severe sporadic neurofibromatosis type 2 (NF2) is typically within childhood; however, there is poor awareness of presenting features in young children, potentially resulting in delayed diagnosis and poorer outcome. We have reviewed presentation of sporadic paediatric NF2 to raise awareness of early features, highlighting those requiring further investigation. Design: Patients diagnosed with NF2 at age ≤16 and seen between 2012 and 2015 were notified via the British Paediatric Neurology Surveillance Unit or identified through the English NF2 service. Results: Epidemiological data estimate that 1 in 110 611 births are affected with childhood-onset NF2. Notes of 32 patients with sporadic NF2 were reviewed. Of those presenting under the age of 5, 89% (17/19) had ocular, 74% (14/19) dermatological and 58% (11/19) neurological signs; in 84% (16/19) features were multisystemic. Sixty-six per cent (21/32) had ≥1 atypical feature, including cerebellar hypoplasia in three cases (9%) and focal cortical dysplasia in five out of seven seizure-related presentations. Five cases presented with a sometimes transient or intermittent cranial nerve mononeuropathy. The mean delay to diagnosis was 3.16 years; in eight cases (25%) this exceeded 6 years. Most significant delay occurred in mononeuropathy, ophthalmological and/or seizure presentations, with a mean delay of 3, 4.5 and 6 years, respectively. Eighty-four per cent (27/32) of cases needed intervention in childhood. Conclusions: All non-vestibular schwannoma NF2 presentations in childhood had significant diagnostic delay. We emphasise the importance of detailed assessment of skin and eyes in unusual presentations and propose an aide to prompt timely referral to specialist services.